Reduced expression of α‐synuclein in alcoholic brain: influence of SNCA‐Rep1 genotype. (13th September 2012) - Janeczek, Paulina; MacKay, Rachel K.; Lea, Rodney A.; Dodd, Peter R.; Lewohl, Joanne M.
Abstract α‐Synuclein has recently been implicated in the pathophysiology of alcohol abuse due to its role in dopaminergic neurotransmission. In these studies, genetic variability in the α‐synuclein gene influences its expression which may contribute to susceptibility to chronic alcohol abuse. Real‐time PCR was used to quantify α‐synuclein mRNA expression in autopsy samples of human dorsolateral prefrontal cortex. Because of the association between length of the α‐synuclein‐repeat 1 microsatellite marker and expression levels of the gene, this marker was genotyped in a Caucasian sample of 126 controls and 117 alcoholics using capillary gel electrophoresis. The allele and genotype frequencies of α‐synuclein‐repeat 1 marker differed significantly between alcoholics and controls. Alcoholics had greater frequencies of the shortest allele found (267 bp). The shortest allele of the α‐synuclein‐repeat 1 marker was associated with decreased expression of α‐synuclein in prefrontal cortex. Individuals with at least one copy of the 267 bp allele were more likely to exhibit an alcohol abuse phenotype. These results suggest that individuals with the 267 bp allele may be at increased risk of developing alcoholism and that genetic variation at the α‐synuclein‐repeat 1 locus may influence α‐synuclein expression in the prefrontal cortex.